Modern diatom assemblages from lake sediments in the boreal–arctic transition region near the Mackenzie Delta, N.W.T., Canada - Koivo, L. K.; Ritchie, J. C. (Canadian Journal of Botany, 1978)
Surface lake mud samples from 20 lake sites across the transition from northern boreal forest to tundra, near the Mackenzie Delta, N.W.T., yielded 284 taxa of diatoms of wide-ranging, mainly subarctic–boreal–nemoral geographical affinity. The ionic composition of the water column shows that 17 of the lakes are oligotrophy with roughly similar diatom assemblages. Distinctive diatom assemblages were recorded only from the three chemically exceptional lakes, saline, meromictic, and slightly N enriched, respectively. The ratio of Araphidineae to Centrales proved to have little use in classifying these particular lakes, although it has been effective in other geographical regions.